The significance of the use of Ochre in the Natufian and Pre-Pottery Neolithic cultures in the territory of the Near East - Kościuk, Julia (Acta Archaeologica Lodziensia, 2018)
Ochre, consisting of iron oxides or hydroxides, is an non-toxic and chemically stable mineral, that could be used in many ways. Firstly, it is connected to sacral context, as it occurred in many graves from Natufian and Pre-Pottery Neolithic cultures on the terrain of Near East. But exact analysis of the phenomenon indicate, that the ochre was also common in usage contexts. Because of its antiseptic and drying features, it was used in medicine and during the processing of hides. Ochre has also been traced in mastics, used to fit a segment tool into wooden or bone handles. Further theories are based on ethnographic analogies.